The association between circulating irisin levels and osteoporosis in women: a systematic review and meta-analysis of observational studies - Shen, Xiaoyang; Chen, Yan; Zhang, Jing; Yang, Meina; Huang, Lu; Luo, Jiaqi; Xu, Liangzhi (Frontiers in Endocrinology, 2024)
Objective: This systematic review and meta-analysis aimed to investigate the association between circulating irisin levels and osteoporosis in women, exploring irisin's potential role in the pathophysiology and management of osteoporosis. Method: We searched PubMed, Embase, Web of Science, Cochrane Library, CNKI, WanFang, and VIP databases up to January 2023. The inclusion criteria were observational studies reporting on circulating irisin levels in women. The standardized mean difference (SMD) and correlation coefficients with a 95% confidence interval (CI) were used as the main effect measures under a random-effects model. Heterogeneity was evaluated using the Cochrane Q statistic and the I 2 statistics. Subgroup analysis and univariate meta-regression analysis were performed to identify the sources of heterogeneity. The quality of the included study was assessed by the Newcastle-Ottawa Score. The quality of evidence was evaluated using the GRADE system. Publication bias was assessed using Begg's and Egger's test, and the trim-and-fill method. Sensitivity analysis was performed to assess the stability of the results. Results: Fifteen studies with a total of 2856 participants met the criteria. The analysis showed significantly lower irisin levels in postmenopausal osteoporotic women compared to nonosteoporotic controls (SMD = -1.66, 95% CI: -2.43 to -0.89, P < 0.0001; I 2 = 98%, P < 0.00001) and in postmenopausal individuals with osteoporotic fractures than in non-fractures controls (SMD = -1.25, 95% CI: -2.15 to -0.34, P=0.007; I 2 = 97%, P < 0.00001). Correlation analysis revealed that irisin levels positively correlated with lumbar spine BMD (r =0.37, 95% CI: 0.18 to 0.54), femoral BMD (r =0.30, 95% CI: 0.18 to 0.42), and femoral neck BMD (r =0.31, 95% CI: 0.14 to 0.47) in women. Despite significant heterogeneity, the robustness of the results was supported by using the random effects model and sensitivity analysis. Conclusions: The current evidence suggests that lower irisin levels are significantly associated with osteoporosis and fracture in postmenopausal women, suggesting its utility as a potential biomarker for early detection of osteoporosis and therapeutic target. However, further high-quality prospective research controlling for confounding factors is needed to clarify the relationship between irisin levels and osteoporotic outcomes.